(untitled) (Altre Modernità, 2016)
The movements for human rights have focused much of their recent claims on the freedom to decide over the body, from a speech based on the affirmation of the individual self as his owner. States and individuals appear to dispute the custody of the organism, ones justifying life as a not delegable instance of modern governmental rationality, others defending the property of the body as a condition for the exercise of their rights and liberties. "My body is mine" and "In my body I decide" are some of the slogans that note the emergence of the body as an ego property, whose starting point can be found in the liberal doctrines, basis of certain claims for the exercise of freedoms and individual rights. In this paper we present the conceptual and theoretical implications that work affirming the discourses about the right to decide about the own body, showing a liberal logic that makes the individual, at the same time, his owner and his property, and that is conjugated to a State that claimes the control of its population’s destiny, and which is required to ensure equal welfare to its citizens. For this analysis we will present some significant elements of Uruguayan contemporary politics, specifically those related to individual rights of body.